Figurative Language in “The Beginning After The End” Volume 10 Novel by Turtleme - Arfani, Sri; Laksono, Muhammad Rino Adi (STIBA IEC JAKARTA, 2024)
The use of figurative language in a novel is a powerful tool to enhance reading experience by employing metaphor, hyperbole, personification, and other figures of speech. The aim of this research is to discover the types of figurative language, the most frequent type of figurative language, and the main function of figurative language in The Beginning After The End Volume 10 novel by TurtleMe. This research uses qualitative research method. The theory in this research is based on a theory proposed by Perrine (1969). Based on the analysis result, study reveals that there are 10 types of figurative language with 90 data in total. They are simile (37 data), metaphor (9 data), personification (11 data), apostrophe (4 data), hyperbole (7 data), synecdoche (7 data), metonymy (7 data), irony (3 data), paradox (3 data), and symbol (2 data). Simile is the most frequent type of figurative language in the novel. Meanwhile, bringing additional imagery is the main function of figurative language in the novel. By shedding light on the use of figurative language in The Beginning After The End Volume 10 novel, this thesis provides valuable insights for educators and literary enthusiasts